INFECTIOUS CELIAC ARTERY ANEURYSM — A RARE CLINICAL ENTITY - Coelho, Andreia Pires (2019)
Introduction: Infectious celiac artery aneurysm (ICAA) is an extremely rare diagnosis, and only a few cases have been reported in the literature to date. We aimed to review this rare clinical entity, focusing on diagnosis and treatment strategies.Methods: A systematic literature review was performed using MEDLINE database according to the PRISMA guidelines.Results: A total of 11 cases of ICAA were identified in the literature to date. Treatment options were extremely variable and included both open and endovascular surgery. Open surgery included aneurysm ligation or aneurysmectomy with or without revascularization with bypass. Endovascular options are increasingly used and include embolization of the aneurysm and collaterals, stentgraft exclusion of the ICAA and in one case report, Chimney technique was used to exclude the aneurysm maintaining celiac trunk patency. Unsurprisingly, antibiotherapy was consistently an essential part of the treatment strategy.Conclusions: Due to the rarity of ICAA, natural history is unclear. Still, surgical treatment is unanimous regardless of aneurysm size. Short term results of endovascular treatment are encouraging, but endovascular implantation of prosthetic material in an infected environment is a concern, so lifelong antibiotherapy and close monitoring are advisable.